CORPORATE GOVERNANCE OF HIGHER EDUCATION INSTITUTIONS IN THE CONTEXT OF GLOBALIZATION CHANGES - Галина Назарова; Інна Дибач; Нікіта Назаров (Економіка та суспільство, 2025)
The article explores the theoretical and methodological foundations for implementing corporate governance in higher education institutions in the context of globalization and institutional transformation. It highlights a paradigm shift in university governance toward models typical of commercial organizations, driven by internal and external factors. Corporate governance is presented as a tool to improve institutional efficiency, transparency, and stakeholder balance. Particular attention is paid to the concept of “corporate governance in HEIs” as the social integration of educational participants through partnership and performance. The systemic-process approach is justified as the most relevant model in dynamic educational environments. It concludes that corporate governance transforms universities into competitive, innovative market actors that build social capital, contribute to sustainable development, and establish effective ties with business, government, and civil society.